Adição de fósforo (P) em catalisadores NiMo, suportados em γ-Al2O3, Al2O3/TiO2 e TiO2 - efeito na hidrodessulfurização do tiofeno - Zanotello, Tatiane Cristina (2013)
Mo, NiMo or NiMoP HDS catalysts were supported on Al2O3, Al2O3-TiO2 or TiO2. These supports were synthesized via sol-gel and in the case o TiO2 it was used a commercial sample. The active phases were introduced by impregnation. Supports and catalysts in the oxide form were characterized by X-ray diffraction (XRD), diffuse reflectance UV-Vis spectroscopy (DRSUV-Vis), thermogravimetric analyses (TG), temperature-programmed reduction with H2 (TPR-H2), N2 adsorption/desorption, energy dispersive X-ray spectroscopy (EDS), X-ray fluorescence (XRF), temperature-programmed desorption of NH3 (TPD-NH3), high resolution transmission electron microscopy (HRTEM) and evaluated at 300°C in the HDS of thiophene, used as a model molecule. Alumina presented a high specific surface area and meso/macroprous characteristics, allowing a high dispersion of the active phases, as was evidenced by XRD and DRSUV-VIS data. A HRTEM image of a NiMo/Al2O3 catalyst showed the presence of crystalline MoS2 whose activity was substantially promoted by the presence of Ni. The NiMo catalysts were active in the HDS of thiophene, however, the activity was enhanced significantly by the incorporation of P. This result corroborates the positive influence of P in the preparation of HDS catalysts. It was suggested that P must participate as promoter in the formation of the NiMoS phase during the sulfidation process of the Ni and Mo oxides. The supported NiMoP catalysts prepared in this work were more active than a commercial NiMoP/ Al2O3 catalyst, with this result validating the preparation procedures used here. The titania addition in the alumina framework led to NiMo catalysts possessing lower activity. That behavior was attributed to the formation of Ni and Mo sulfides without interaction diminishing the generation NiMoS phase, which is highly active in the HDS of sulfured organic compounds.